2020
DOI: 10.1038/s41586-020-2750-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of cGAS inhibition by the nucleosome

Abstract: histones in situ, which were partially lost upon aclarubicin treatment (Extended Data Fig. 1c, d). Thus, histones appear to dynamically engage cGAS in the nucleus.Consistent with prior work [13], functional analysis of cGAS in vitro enzymatic activity revealed that mononucleosomes (hereafter nucleosomes) inhibited DNA-induced cGAMP synthesis (Extended Data Fig. 1e). Likewise, compact chromatin fibres (12-mer nucleosome arrays) suppressed cGAS activity (Extended Data Fig. 1e). H2A-H2B dimers also had an inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(157 citation statements)
references
References 52 publications
7
149
1
Order By: Relevance
“…In parallel with this study, five other groups also reported on the cryo-EM structures of human and mouse cGAS-nucleosome complexes. [11][12][13][14][15] We note that the 2:2 and higher-order assemblies mediated by cGAS site C are observed in all three human cGAS-NCP structures 9,12,15 but not in their mouse counterparts. 11,13,14 Consistent with this distinction, site C has been shown to be an evolutionarily strengthened DNA-binding interface when proceeding from mouse to humans.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In parallel with this study, five other groups also reported on the cryo-EM structures of human and mouse cGAS-nucleosome complexes. [11][12][13][14][15] We note that the 2:2 and higher-order assemblies mediated by cGAS site C are observed in all three human cGAS-NCP structures 9,12,15 but not in their mouse counterparts. 11,13,14 Consistent with this distinction, site C has been shown to be an evolutionarily strengthened DNA-binding interface when proceeding from mouse to humans.…”
mentioning
confidence: 64%
“…The studies discussed here 9,[11][12][13][14][15] provide compelling evidence of cGAS sequestration and inhibition by the nucleosome, with such nuclear tethering trapping cGAS in an inactive conformation. Fig.…”
mentioning
confidence: 73%
“…The structure of the cGAS catalytic domain bound to a nucleosome has been resolved by many groups, which reveals that cGAS inhibition in the nucleus is mediated by interaction through histone 2A-2B but not through nucleosomal DNA binding. The interaction between cGAS and histone embeds the cGAS DNA-binding site B, and prevents the formation of active cGAS dimers (108)(109)(110). Kujirai et al has reported a cryo-electron microscopy structure with two cGAS molecules bridging two nucleosome core particle (NCP).…”
Section: Cgas-sting Pathwaymentioning
confidence: 99%
“…2E). The subcellular distribution of cGAS is closely related to its function [17][18][19][20][21] . At rst we con rmed that cGAS protein of T24 and TCCSUP cell lines was mainly located in nucleus (Fig.…”
Section: Cisplatin Induced Dsdna May Function As An Important Role Inmentioning
confidence: 99%
“…Liu et al found that the nuclear translocation of cGAS in THP-1 and HeLa cells can affect its functions by suppressing homologous-recombination-mediated repair 16 . Studies have also shown that the binding capacity of cGAS to nucleosomes is much greater than that of cGAS to dsDNA [17][18][19][20][21] . This can explain why the cGAS-STING signal is not signi cantly activated during mitosis when a large amount of dsDNA is exposed to the cytoplasm due to the dissolved nuclear membrane.…”
mentioning
confidence: 99%